2014
DOI: 10.2217/nnm.13.71
|View full text |Cite
|
Sign up to set email alerts
|

Improved Transfection in Human Mesenchymal Stem Cells: Effective Intracellular Release of pDNA by Magnetic Polyplexes

Abstract: The process of pDNA liberation may significantly influence the efficiency of the transfection vector. Therefore, it should be carefully considered when creating novel gene delivery agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…To further improve uptake efficiencies, different NP ratios and MNP concentrations were tested and analyzed by flow cytometry while miR amount was kept constant (5 pmol/cm 2 miR, Figure 3C,D). In our previous experiments with delivery of plasmid DNA using the same carrier system, we found that NP ratio 2.5 was optimal for transfection of hMSCs [28]. Nevertheless, miR and plasmid DNA differ in terms of structure, function and stability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further improve uptake efficiencies, different NP ratios and MNP concentrations were tested and analyzed by flow cytometry while miR amount was kept constant (5 pmol/cm 2 miR, Figure 3C,D). In our previous experiments with delivery of plasmid DNA using the same carrier system, we found that NP ratio 2.5 was optimal for transfection of hMSCs [28]. Nevertheless, miR and plasmid DNA differ in terms of structure, function and stability.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, we took advantages of a labeling method for DNA containing transfection complexes, recently developed by our group. This technique does not affect transfection efficiency and cell viability [28]. Therefore, it is a reliable method for intracellular imaging of transfection processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for our studies, as well as for clinical trials, hMSCs so far were expanded in vitro [21, 22, 25]. However, in vitro expansion of primary hMSCs is a costly and time-consuming procedure.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this would facilitate MCNP complexation with negatively-charged plasmid DNA and induce endosomolysis within the cytoplasm [37]. To minimize cytotoxicity while maximizing transfection efficiency, we used 10 kDa branched PEI, which has previously been demonstrated to be biocompatible with stem cells [21, 38]. The resulting water soluble PEI-coated MCNPs (MCNP-PEI) had a hydrodynamic size of 117.2 ± 37 nm (polydispersity index [PDI] = 0.177) as measured by dynamic light scattering (DLS) and a zeta potential of +44.23 ± 0.72 mV (Figures 2C and S2A).…”
Section: Resultsmentioning
confidence: 99%